Water quality of Bakun Hydroelectric Dam Reservoir, Sarawak, Malaysia, during the construction of Murum dam / Lee Nyanti, Teck-Yee Ling and Theresa Muan - Lee, Nyanti; Ling, Teck-Yee; Muan, Theresa (Universiti Teknologi MARA, Pulau Pinang, 2015)
Since Bakun Hydroelectric Reservoir was filled, there has not been any published literature on its water quality. A previous study conducted during its filling stage showed that the DO level dropped very rapidly and the water was turbid. Since water quality was expected to improve over time, this study was carried out. Six stations and 3 depths at each station were investigated. Results show that dissolved oxygen at 0.5 m depth ranged from 6.25 to 7.02 mg/L but the water was anoxic at 15 m and 30 m depths. pH at 0.5 m depth in the reservoir ranged from 7.37 to 7.73 and decreased with depth to acidic condition. In the reservoir, turbidity at the subsurface were 0 NTU but at 15 m depth, it ranged from 19.5-105.4 NTU. BOD5 were higher at 15 m and 30 m than 0.5 m depth. There was some improvement of water quality for stations in the reservoir compared to the previous study, especially in terms of pH and DO, but turbidity was still high at deeper regions. Stations in the Murum River and its downstream showed extremely high turbidity attributed to the construction of the Murum Dam. Thus, the river was not suitable for sensitive aquatic organisms.